Pengaruh Dimensi Pengungkapan Corporate Social Responsibility Terhadap Future Institutional Ownership - Rizky Eriandani (Fakultas Ekonomika dan Bisnis Universitas Kristen Satya Wacana, 2014)
Corporate social responsibility practice becomes important subject in company`s activity, because it will affect the company's reputation. Besides, institutional investors likely prefer to invest in companies that have a social responsibility as it is considered to increase the legitimacy and future performance. This study aims to investigate the effect of CSR disclosure on institutional ownership. We use percentages ownership to measure institutional ownership. CSR measurement instrument used in this study adopted a previous research. The instrument comes from research Hackston and Milne, which was adjusted with Bapepam regulation in Indonesia. We also divided CSR disclosures in four sub-dimensions. The samples used in this research were 115 listed agriculture, mining, and manufacturing companies in indonesian Stock Exchange which studied during the years of 2010. Using SPSS 20, The analysis methods of this research used multiple regression analysis. Studies shows that not all dimensions of CSR disclosure effect on institutional ownership. Only product dimensions of CSR disclosures has a significant positive impact on institutional ownership. However, this paper fail to find any significant impact of another CSR dimensions. Thus, our study suggests that the dimensions of the product can affect investment decisions. In contrast, institutional investors have not focused on environment, employee relation, and community activities in investment decisions.